Prove that sin(x)^2 - 5cos(x)^2 = 6sin(x)^2 - 5

5 = 5(cos(x)^2 + sin(x)^2) = 5cos(x)^2 + 5sin(x)^2=> 5 - 5cos(x)^2 = 5sin(x)^2=> sin(x)^2 + 5 - 5cos(x)^2 = 6sin(x)^2=> sin(x)^2 - 5cos(x)^2 = 6sin(x)^2 - 5

Related Further Mathematics GCSE answers

All answers ▸

Find dy/dx when y=2x^(4)+3x^(-1)


Show that (n^2) + (n+1)^2 + (n+2)^2 = 3n^2 + 6n + 5, Hence show that the sum of 3 consecutive square numbers is always 2 away from a multiple of 3.


How do I know I can multiply two matrices and if so, how do I do it?


f(x) = 3x^3 – x^2 – 20x – 12 (a) Use the factor theorem to show that (3x + 2) is a factor of f(x). [2 marks] (b) Factorise f(x) fully. [3 marks]


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences